Antiplasmodial and Antimalarial Activity of 3, 5‐Diarylidenetetrahydro‐2H‐pyran‐4(3H)‐ones via Inhibition of Plasmodium falciparum Pyridoxal Synthase. (8th November 2022) - Moorthy, Hariharan; Yadav, Mamta; Tamang, Nitesh; Mavileti, Sai Kiran; Singla, Labhini; Choudhury, Angshuman Roy; Sahal, Dinkar; Golakoti, Nageswara Rao
Abstract: A series of 22 different 3, 5‐diarylidenetetrahydro‐2 H ‐pyran‐4(3 H )‐ones (DATPs) were synthesized, characterized, and screened for their in vitro antiplasmodial activities against chloroquine (CQ)‐sensitive Pf 3D7, CQ‐resistant Pf INDO, and artemisinin‐resistant Pf MRA‐1240 strains of Plasmodium falciparum . DATP 19 ( 3, 5‐bis(4‐hydroxy‐3, 5‐dimethoxybenzylidene)tetrahydro‐2 H ‐pyran‐4(3 H )‐one) was found to be the most potent (IC50 1.07 μM) against Pf MRA‐1240, whereas 21 (3, 5‐bis(3, 4, 5‐trimethoxybenzylidene)tetrahydro‐2 H ‐pyran‐4(3 H )‐one) showed IC50 values of 1.72 and 1.44 μM against Pf 3D7 and Pf INDO, respectively. Resistance indices (RI) as low as 0.2 to 0.5 for 10 (3, 5‐bis(4‐nitrobenzylidene)tetrahydro‐2 H ‐pyran‐4(3 H )‐one) and 20 (3, 5‐bis(3‐nitrobenzylidene)tetrahydro‐2 H ‐pyran‐4(3 H )‐one), and <1 for most other DATPs reveals their greater potency against resistant strains than the sensitive one. The single‐crystal XRD data for DATP 21 are reported. In silico support was obtained through docking studies. Killing all three strains within 4–8 h, these DATPs showed rapid kill kinetics toward the trophozoite stage. Furthermore, DATP 18 (3, 5‐bis(quinolin‐4‐ylmethylene)tetrahydro‐2 H ‐pyran‐4(3 H )‐one) inhibited Pf Pdx1 enzyme activity with IC50 20.34 μM, which is about twofold lower than that (IC50 43 μM) for an already known inhibitor 4PEHz. At an oral dose of 300 mg/kg body weight, DATPs 19 and 21 were found to be nontoxic to mice, and at 100 mg/kg body weight, DATP 19 was found to suppress parasitaemia, which led to an increase in median survival time by three days relative to untreated control mice in a malaria curative study. Abstract : In the quest for new leads against malaria, the 3, 5‐diarylidenetetrahydro‐2 H ‐pyran‐4(3 H )‐ones (DATPs) reported in this work show good promise, with six compounds in particular having IC50 values less than 5 μM, low resistance indices (∼<1) and high selectivity (up to 40‐fold) against P. falciparum .